Indian Women struggle against the Obstructions of a Closed Society with special reference to Sudha Murthy Novels - Jyothi, Polamrasetti; Vijayanand, Dr. A. (The journal of contemporary issues in business and government, 2023)
The struggle of Indian women in Sudha Murthy’s novels against the oppressive mechanisms of a closed society is the subject of this paper. Women all over the country struggle to maintain their dignity in life. Employment, health care, and property rights are just a few of the issues women face in everyday life. Therefore, women’s empowerment remains a distant goal in India. This paper discusses how female characters in Sudha Murthy’s books are marginalized and exploited. Women and girls all over the world are still subjected to violence, discrimination, inequality, and poverty. Despite the fact that they have laid the foundation of society, they have not been able to secure their true position in life. In fact, women and girls are frequently unable to assert their fundamental rights. The women’s movement, which is made up of women who are empowered both individually and collectively to challenge patriarchal norms,address the root causes of inequality, and demand the full range of their rights, would benefit from the awareness that this research paper would help to raise.